A loan-level analysis of financial resilience in Mexico - Cantú, Carlos; Lobato, Roberto; López, Calixto; López-Gallo, Fabrizio (Journal of Banking & Finance, 2022)
Using loan-level data from the Mexican credit registry, we evaluate how bank characteristics affect the transmission of domestic and foreign shocks to credit supply. We find that banks with higher capital, liquidity, profitability, long-term funding and deposit funding show a smaller response to shocks. By contrast, banks with high credit risk and foreign funding show a larger response. Second, foreign banks respond more sensitively to shocks compared to domestic banks. Finally, the credit supply to firms that are small, have higher credit risk and weak banking-relationships shows a larger response to shocks. The evolution of bank characteristics in Mexico, through the lens of these results, has strengthen the resilience of its financial system.